Pengaruh Penerapan Akuntansi Manajemen Lingkungan Terhadap Nilai Perusahaan di Indonesia : (Studi Empiris Perusahaan Manufaktur di Jawa Barat) - Bahtiar Effendi (Politeknik Ganesha Medan, 2021)
This study aims to analyze the factors of environmental management accounting on firm value in West Java. The phenomenon of companies having high firm values was also found with conditions inversely proportional to the low practice of implementing environmental conservation responsibility. The population of this study were all manufacturing companies located in West Java for the period 2018-2019 and based on the purposive sampling method, a sample of 120 respondents was obtained. By using multiple linear regression analysis as a research method, it is found that there is a significant positive influence between the application of environmental management accounting which is proxied through the aspects of material input, transportation, supplier assessment, and other aspects of firm value. Besides, it is found that the results of a significant negative effect between the application of environmental management accounting are proxied through the aspects of non-product output, compliance, and environmental complaints mechanisms on firm value. Furthermore, based on the simultaneous test results, it was found that the application of environmental management accounting was proxied through the aspects of material input, non-product output, compliance aspects, transportation aspects, other aspects, supplier assessment, and environmental complaint mechanisms simultaneously affected on firm value. Agency theory was successfully applied in this study, this is indicated by the results obtained, namely, the application of environmental management accounting is proven to affect the level of firm value.